PEMETAAN INDUSTRI “LEMEA” MAKANAN TRADISIONAL SUKU REJANG DI PROVINSI BENGKULU - Dewi, Kurnia Harlina; Silsia, Devi; Susanti, Laili; Hasanuddin, Hasanuddin (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2014)
Traditional foods processed by recipes taught for generations. The material used is derived from the local area, therefore the food produced is also palatable to the local community. The purpose of this study was to obtain deployment of “Lemea”, the traditional food of Bengkulu Province as a basis for the agro-industry design of traditional food standardized (raw materials and processes) of the Rejang tribe, to produce a consistent product quality, hygienic and attractive, so it can compete with other package food products as well as preserving traditional foods. The research method used is the method of direct survey taken in nine districts in the Bengkulu province through interviews. The data obtained are plotted into the map of the area and are associated with secondary data. Survey result shows that the Lemea home industry only found in five districts of the Bengkulu province, i.e. district of Central Bengkulu, district of Northern Bengkulu, district of Kepahiang, district Rejang Lebong and district of South Lebong. The main raw materials used in each district are varied on types and tastes. Additional material (fish) and spices used also varies according to local conditions. The length of time of fermentation conducted also varies and there are differences a source of glucose (addition and without addition of rice porridge ) in the fermentation.